Highly reliable triboelectric bicycle tire as self-powered bicycle safety light and pressure sensor. (March 2022) - Son, Jin-ho; Heo, Deokjae; Song, Yeonsu; Chung, Jihoon; Kim, Banseok; Nam, Woochul; Hwang, Patrick T.J.; Kim, Dongseob; Koo, Bonwook; Hong, Jinkee; Lee, Sangmin
Abstract: Because of the COVID-19 pandemic, the number of bicycle users has increased, raising concerns regarding bicycle safety. Although various small electronic devices have been used to ensure bicycle safety, such devices require an external battery, which introduces certain limitations such as recharging requirements. Several researchers have investigated methods to sustainably harvest energy from bicycles. Triboelectric-generator-based solutions, which can utilize the mechanical motion of a rolling tire can serve as the auxiliary power source of small electronics or self-powered sensors. However, research on practical and reliable bicycle-related triboelectric nanogenerators is limited. In this study, a triboelectric bicycle tire (TBT) was developed, considering the actual material/structure of commercial bicycle tires, and the novel electricity-generation mechanism was clarified. As the TBT system had a fully inserted (packaged) structure, it could generate extremely stable electrical output for 120, 000 cycles. The electrical performance was quantitatively analyzed depending on the design parameters and riding situation. The findings demonstrated that the TBT system can be effectively used to enhance bicycle safety; according to the peak magnitude and waveform data, the TBT system can function as a self-powered bicycle pressure sensor. Second, the freestanding-mode TBT system can be utilized as a self-powered bicycle safety light in real time, demonstrated by its ability to power LEDs. Graphical Abstract: ga1 Highlights: Highly practical and reliable triboelectric bicycle tire system considering the actual structure/materials of commercial bicycle tires. First study to report on a novel electricity generation mechanism that prevents electron leakage. Quantitative analysis depending on design parameters and actual riding situation. Two bicycle safety strategies based on the TBT system: self-powered bicycle safety light and pressure sensor.